The Project of Democracy - Keyssar, Alexander (Maine Policy Review, 2002)
This article is an address given at the May 2002 Maine Town Meeting sponsored by the Margaret Chase Smith Library in Skowhegan. Alexander Keyssar chronicles the advances and contractions of democratic political rights in American history. While on balance, this is a story of progress, it is not, Keyssar argues, unilinear, nor one that is completed. Although arguably late for the world’s “greatest democracy,” by the 1970s the United States had achieved universal suffrage. Today, however, the tug between democratic and anti-democratic forces continues. The contest is no longer over voting rights but over the procedures and rules governing elections (i.e., election reform and redistricting). Keyssar argues we must continue to fight for the expansion of democratic rights; it is an ongoing project, one in which we will never be finished.